Overseas background executives and enterprise ESG performance -The moderating effect of the executive pay gap - Baoping Liu; Haohao Wei; Jing Liu (PLoS ONE, 2025)
Enhancing corporate ESG (Environmental, Social, and Governance) performance is a critical issue garnering widespread attention across various sectors. This research examines the impact of executives with overseas backgrounds on corporate ESG performance, utilizing a two-way fixed-effects model with data from Chinese A-share listed companies in Shanghai and Shenzhen spanning from 2008 to 2022. The findings indicate that: (ⅰ) executives with overseas backgrounds positively influence corporate ESG performance, with this effect amplifying as the proportion of such executives within the executive team increases; (ⅱ)both internal and external pay gaps significantly positively moderate the relationship between overseas background executives and corporate ESG performance; (ⅲ) the influence of overseas executives on ESG performance is more pronounced in state-owned enterprises, large-scale firms, firms in the eastern region, and those in high-pollution industries. This study expands the understanding of factors affecting corporate ESG performance, offers empirical insights for listed companies aiming to enhance their ESG performance, and provides valuable implications for executive team construction, executive compensation strategies, government talent policies, and the pursuit of high-quality economic development.